In Vivo Photoacoustic Imaging of Livers Using Biodegradable Hyaluronic Acid‐Conjugated Silica Nanoparticles. (14th April 2018) - Lee, Donghyun; Beack, Songeun; Yoo, Jounghyun; Kim, Su‐Kyoung; Lee, Changho; Kwon, Woosung; Hahn, Sei Kwang; Kim, Chulhong
Abstract: The diagnosis of liver diseases is generally carried out via ultrasound imaging, computed tomography, and magnetic resonance imaging. The emerging photoacoustic imaging is an attractive alternative to diagnose even early stage of liver diseases providing high‐resolution anatomical and functional information in deep tissue noninvasively. However, the liver has insufficient photoacoustic contrast due to low optical absorbance in the near‐infrared windows. Here, a new hyaluronate–silica nanoparticle (HA–SiNP) conjugate for liver‐specific delivery and imaging for the diagnosis of liver diseases is developed. The HA–SiNP conjugates show high liver‐specific targeting efficiency, strong optical absorbance near‐infrared windows, excellent biocompatibility, and biodegradability. The liver‐specific targeting efficiency is verified by in vitro cellular uptake test, and in vivo and ex vivo photoacoustic imaging. In vivo photoacoustic imaging shows that photoacoustic amplitude in the liver injected with HA–SiNP conjugates is 4.4 times higher than that of the liver injected with SiNP. The biocompatibility and biodegradability of HA–SiNP conjugates are verified by cell viability test, optical spectrum analysis of urine, and inductively coupled plasma‐mass spectroscopy (ICP‐MS) analysis. Taken together, HA–SiNP conjugates may be developed as a promising liver targeted photoacoustic imaging contrast agent and liver‐targeted drug delivery agent. Abstract : A new hyaluronate–silica nanoparticle (HA–SiNP) conjugate for liver‐specific delivery and imaging for the diagnosis of liver diseases is developed. The HA–SiNP conjugates show high liver‐specific targeting efficiency, strong optical absorbance near‐infrared windows, excellent biocompatibility, and biodegradability. The liver‐specific targeting efficiency is verified by an in vitro cellular uptake test, and in vivo and ex vivo photoacoustic imaging.